2018
DOI: 10.1002/rcm.8119
|View full text |Cite
|
Sign up to set email alerts
|

Development of a multi‐functional concurrent assay using weak cation‐exchange solid‐phase extraction (WCX‐SPE) and reconstitution with a diluted sample aliquot for anti‐doping analysis

Abstract: The method was validated and applied to real samples in accordance with the external quality assessment scheme of WADA and to the previously reported samples that had provided positive test results. This novel method using hybrid sample preparation and LC/MS could be useful to screen multiple classes of the 264 targeted substances in anti-doping analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 41 publications
(93 reference statements)
2
16
0
1
Order By: Relevance
“…Moreover, it was demonstrated that the implementation of lower molecular mass peptides (and peptide-related compounds) into comprehensive multi-target initial testing procedures is possible, either by simple dilute-and-inject approaches or combined analysis of SPE extracts with diluted urine specimens. [6][7][8] Although the provided limits of detection (LODs) meet World Anti-Doping Agency (WADA) requirements (minimum required performance level; MRPL = 2 ng/mL), the sensitivity of these assays is clearly inferior to peptide-specific stand-alone approaches, according to limitations of type and pH value of mobile phase as well as applied mass spectrometric acquisition modes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was demonstrated that the implementation of lower molecular mass peptides (and peptide-related compounds) into comprehensive multi-target initial testing procedures is possible, either by simple dilute-and-inject approaches or combined analysis of SPE extracts with diluted urine specimens. [6][7][8] Although the provided limits of detection (LODs) meet World Anti-Doping Agency (WADA) requirements (minimum required performance level; MRPL = 2 ng/mL), the sensitivity of these assays is clearly inferior to peptide-specific stand-alone approaches, according to limitations of type and pH value of mobile phase as well as applied mass spectrometric acquisition modes.…”
Section: Introductionmentioning
confidence: 99%
“…13 Among the several extraction methods, SPE involves less sample manipulation, which simplifies the pretreatment procedure and requires less proficiency from the analyst. 20 Mixed-mode weak cation exchange SPE (WCX-SPE) involves reverse phase and WCX that has proven to be an effective approach to extract peptides from urine. 5 Thomas et al reported on a WCX-SPE method to extract GHRPs from urine that inspired the extraction method utilized here.…”
Section: Sample Preparationmentioning
confidence: 99%
“…These fall into several categories, each with distinct pharmacological profiles, chemical properties, and year‐by‐year increasingly specific requirements for their detection 2 . With recent technological advances in both liquid chromatography and mass spectrometry (LC‐MS), a great deal of effort has been directed toward development of multiclass initial testing procedures (ITP) to streamline analytical workflows in antidoping laboratories 3–32 …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the second group does require preconcentration via liquid–liquid extraction (LLE) or solid phase extraction (SPE), which may or may not be preceded by enzymatic deconjugation. For this reason, multiclass ITPs had initially been developed utilizing triple quadrupole mass spectrometry (LC‐MS/MS) and two complimentary preparations such as dilute‐and‐shoot 3–12 and extraction‐based total fraction assays 13–32 . A comprehensive review has been provided by Thevis et al 33 wherein the former methods would typically cover diuretics, stimulants, narcotics, β‐blockers, and some of the β 2 ‐agonists, whereas the latter would focus on anabolic agents, hormone modulators, fentanyl analogs, synthetic cannabinoids, and glucocorticosteroids.…”
Section: Introductionmentioning
confidence: 99%